Urgensi Ilmu dan Ulama dalam Al-Quran dan Hadis: Sebuah Tinjauan Teoritis - Yuniartin, Titin; Ibad, Achsin; Julhusni, Arda; Darojah, Indah (Trends in Applied Sciences, Social Science, and Education, 2024)
Knowledge is very important for human life because it can increase human dignity. In Islam, seeking knowledge is a form of worship to Allah and there are several specific goals in the process of seeking knowledge. It is clear that the main key to happiness and success both in this world and the hereafter is knowledge. Ulama are those who have or master any knowledge in depth and this knowledge has caused them to have a deep awareness of God and high moral awareness. Ulama are the successors of the struggle of the prophets in spreading goodness and preventing evil. This study uses a qualitative research approach that is a literature study. Data from various references are used as sources of information which are then processed and analyzed. Useful knowledge is knowledge that is taught and practiced to get closer to Allah. The role of Ulama as a knowledgeable person is not only to master the treasures of Islamic knowledge but can also be present in society as a guide for the people. If the ulama are gone, then there is no knowledge in this world either. Useful knowledge will also be useful both in this world and in the hereafter. Knowledge is very important for human life because it can increase human dignity.